Cryo-EM reveals ligand induced allostery underlying InsP3R channel gating. Issue 12 (December 2018) - Fan, Guizhen; Baker, Mariah; Wang, Zhao; Seryshev, Alexander; Ludtke, Steven; Baker, Matthew; Serysheva, Irina
Abstract Inositol-1, 4, 5-trisphosphate receptors (InsP3 Rs) are cation channels that mobilize Ca2+ from intracellular stores in response to a wide range of cellular stimuli. The paradigm of InsP3 R activation is the coupled interplay between binding of InsP3 and Ca2+ that switches the ion conduction pathway between closed and open states to enable the passage of Ca2+ through the channel. However, the molecular mechanism of how the receptor senses and decodes ligand-binding signals into gating motion remains unknown. Here, we present the electron cryo-microscopy structure of InsP3 R1 from rat cerebellum determined to 4.1 Å resolution in the presence of activating concentrations of Ca2+ and adenophostin A (AdA), a structural mimetic of InsP3 and the most potent known agonist of the channel. Comparison with the 3.9 Å-resolution structure of InsP3 R1 in the Apo-state, also reported herein, reveals the binding arrangement of AdA in the tetrameric channel assembly and striking ligand-induced conformational rearrangements within cytoplasmic domains coupled to the dilation of a hydrophobic constriction at the gate. Together, our results provide critical insights into the mechanistic principles by which ligand-binding allosterically gates InsP3 R channel.